1977
DOI: 10.1093/nar/4.4.1083
|View full text |Cite
|
Sign up to set email alerts
|

Preliminary morphological and X-ray diffraction studies of the crystals of the DNA cetyltrimethylammonium salt

Abstract: Double-stranded DNA molecules (molecular weight 2.5 X 10(5) - 5 X 10(5) daltons) have been crystallized from water-salt solutions as cetyltrimethylammonium salts (CTA-DNA). Variation of crystallization conditions results in a production of different types of CTA-DNA crystals: spherulits, dendrites, needle-shaped and faceted rhombic crystals, the latter beeing up to 0.3 mm on a side. X-ray diffraction data indicate that DNA molecules in the crystals form a hexagonal lattice which parameters vary slightly with t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

1979
1979
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 8 publications
0
9
0
Order By: Relevance
“…In addition to this the hydrophobic moieties of the surfactant molecules stabilize the complex through the hydrophobic interactions with the DNA. [15][16][17] Based on the studies carried out on the compaction of doublestranded DNA (ds-DNA) by cationic surfactants, using fluorescence microscopy, three distinguishable regimes of the DNA compaction process are highlighted, depending on the concentration of the cationic surfactant. 1,[18][19][20][21][22][23][24] In the absence of surfactant, DNA molecules in solution exist in extended (coil) conformation with relatively slow wormlike motion.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to this the hydrophobic moieties of the surfactant molecules stabilize the complex through the hydrophobic interactions with the DNA. [15][16][17] Based on the studies carried out on the compaction of doublestranded DNA (ds-DNA) by cationic surfactants, using fluorescence microscopy, three distinguishable regimes of the DNA compaction process are highlighted, depending on the concentration of the cationic surfactant. 1,[18][19][20][21][22][23][24] In the absence of surfactant, DNA molecules in solution exist in extended (coil) conformation with relatively slow wormlike motion.…”
Section: Introductionmentioning
confidence: 99%
“…A number of researchers have shown that in the DNA−surfactant complexes the cationic surfactant molecules bind to the DNA chains through electrostatic interactions. In addition to this the hydrophobic moieties of the surfactant molecules stabilize the complex through the hydrophobic interactions with the DNA. …”
Section: Introductionmentioning
confidence: 99%
“…It has been shown that the 1:1 stoichiometric combination of an anionic polyelectrolyte with a cationic surfactant leads to spontaneous formation of highly organized assemblies. The self-assembled bulk materials exhibit interesting properties such as thermotropic liquid-crystalline behavior, which results from long-range organization on a mesoscopic length scale. Also, DNA, which is an anionic polyelectrolyte, could be quantitatively precipitated with cationic surfactants in water. The method of precipitating various types of DNA by cationic surfactants has been applied to DNA extraction, concentration, and counting. It was suggested that DNA could be recovered in a native state to form DNA−cationic surfactant complexes with 12-, 14-, and 16-carbon alkyltrimethylammonium bromides No doubt, these studies are very important for understanding the mechanisms of cell transfection and gene therapy.…”
Section: Introductionmentioning
confidence: 99%
“…So far, the only resulting complex structures that have been characterised are a hexagonal structure (which consists of a network of cylindrical surfactant micelles with the DNA rods intercalated in between) and a lamellar structure (when the surfactant has special hydrotope counterions). [7,8] In this Communication, we describe the formation and characterisation of a new cubic phase that contains short DNA chains (i.e., 150 base pairs and a length that is at least equal to the persistence length); this phase is formed using a short-tailed surfactant: decyltrimethylammonium (C 10 TAB).…”
Section: Introductionmentioning
confidence: 99%